New Squarer Circuits and a Current-Mode Full-Wave Rectifier Topology Suitable for Integration - Minaei, Shahram; Yuce, Erkan (Společnost pro radioelektronické inženýrství, 2010)
In this paper, three squarer configurations and a current-mode (CM) full-wave rectifier circuit are suggested. The first and second squarer configurations respectively use two PMOS and two NMOS transistors while the third one employs three PMOS and one NMOS transistors. A CM full-wave rectifier with high output impedance current is developed. All of the proposed circuits provide several advantages such as low number of components and less power consumption. The proposed circuits are simulated using SPICE program to demonstrate their performance and workability.
Keywords: CMOS; squarer circuit; rectifier; current-mode